2015
DOI: 10.1353/hpu.2015.0083
|View full text |Cite
|
Sign up to set email alerts
|

Not Near Enough: Racial and Ethnic Disparities in Access to Nearby Behavioral Health Care and Primary Care

Abstract: Background-Racial, ethnic, and geographical health disparities have been widely documented in the United States. However, little attention has been directed towards disparities associated with integrated behavioral health and primary care services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 54 publications
1
32
0
Order By: Relevance
“…Other mechanisms of delivery, such as telehealth, could have made the program more accessible. Second, patients with fewer resources and greater social disparities are not as likely to access health care or participate in research ; our results are likely biased because of the difficulties of including diverse participants. Third, we had multiple surveys that represented response burdens to some participants who continued in the program (but did not complete the forms).…”
Section: Discussionmentioning
confidence: 96%
“…Other mechanisms of delivery, such as telehealth, could have made the program more accessible. Second, patients with fewer resources and greater social disparities are not as likely to access health care or participate in research ; our results are likely biased because of the difficulties of including diverse participants. Third, we had multiple surveys that represented response burdens to some participants who continued in the program (but did not complete the forms).…”
Section: Discussionmentioning
confidence: 96%
“…Thus, much of the disparity in mental health outcomes across racial and ethnic groups can be explained by socioeconomic status and other neighborhood-level factors such as segregation, social isolation, and exposure to violent crime (Williams andEarl, 2007, Alegria et al, 2015). Further, research on mental health service has shown mental health services are less available in neighborhoods with higher racial and ethnic minority populations, making it more challenging for minority populations to receive treatment (VanderWielen et al, 2015). Stigma and mental health education may also play a role in racial and ethnic disparities in treatment (Batterham et al, 2013).…”
Section: Race and Ethnicitymentioning
confidence: 99%
“…Socioeconomic variables included mean household income, poverty, unemployment, and low educational attainment (Spady et al, 2001;Amone-P'Olak et al, 2009;Reiss, 2013;Center for Behavioral Health Statistics and Quality, 2016). Demographic variables included race, ethnicity, divorce, single parent homes, population density, and Rural-Urban Continuum Codes (RUCC) (Sen, 2004;Hempstead, 2006;Akhtar-Danesh and Landeen, 2007;Alegria et al, 2015;Fontanella et al, 2015;VanderWielen, et al 2015;Nestor et al, 2016). Residential stability was measured using renter-occupied homes and individuals living in a different home during the past twelve months (Cutchin and Churchill, 1999;Barkan et al, 2013).…”
Section: County-level Explanatory Variablesmentioning
confidence: 99%
See 2 more Smart Citations